The grotesque in the works of Federico Fellini and Angela Carter - O'Gara, Maura Rayne (Department of English Language and Literature, 2016)
Chapter one of this thesis attempts to explicate and analyze the controversy that has historically surrounded the grotesque. Contention over the grotesque has existed since the earliest known discourses on the subject by Horace and Vitruvius. The indeterminacy and paradoxical nature of the grotesque, which disturbed these men of antiquity, has continued to generate debate among modern theorists such as Mikhail Bakhtin and Wolfgang Kayser whose ideas serve as touchstones throughout this work. Understandably, theorists, who strive to create systems of ideas which attempt to explain and define phenomena, are drawn to the grotesque. However, they are inevitably placed in the paradoxical position of trying to categorize something which ultimately subverts the conventional logic which underlies that process. Furthermore, the standards of mimesis and decorum, from which the grotesque gets its disruptive force, are subject to society. Societies provide the different conventions and assumptions that determine the form of the grotesque. Therefore, the grotesque will always have to be approached in its historically specific contexts of production and reception. What becomes apparent in analysing the grotesque is that attitudes toward its indeterminacy and paradoxical nature, which transgress the monologic binaries and implied hierarchies of Western thought, reflect the position of the observer or producer of the grotesque. If one espouses the cause of the low, as does Balch tin, then the indeterminacy and paradox of the grotesque provides an egalitarian possibility for the marginalized. If one stands with the status quo, as does Kayser, the transgressing of the definitions and distinctions which support the status quo is experienced as frightening and sinister (Harpham, 73). The differences noted between Kayser and Balch tin as observers of the grotesque may also be made between Federico Fellini and Angela Carter as producers of grotesque texts. The following two chapters of the thesis explore how the grotesque is used in Fellini's films (chapter two) and Carter's novels (chapter three). Carter, like Bakhtin, celebrates the grotesque as a means of empowerment, particularly for women and her work seems to employ the Bakhtinian theory of the carnivalesque. Fellini's films also use images of carnival, but Fellini, like Kayser, sees the grotesque as an isolating aspect of the human condition. Fellini uses the grotesque only to show humanity's alienation from a knowable world, whereas Carter uses it to demonstrate the possibilities of a totally new one. Carter appears to take the Fellinian, Kayserian, negative attitude towards the grotesque and turn it around for her feminist cause. She utilizes the emancipatory aspect of the grotesque inherent in its denial of hierarchy without, however, idealizing it as Bakhtin appears to. She is well aware that carnivals, like her novels, are author(ized). In analyzing the continuum of Fellini's and Carter's works, both artists show an increased dependence on the use of the grotesque combined with postmodern strategies to support their intentions. However, the continuum of Fellini's oeuvre suggests the development of a modernist approach which attempts closure, but faced with the impossibility of final determinacy, turns to the quagmire of simulacra where no meaning is possible. Carter, on the other hand, increasingly uses the grotesque and postmodern strategies not only to reveal and deconstruct oppressive representations, but to allow agency for the reconstruction of new subjectivities. As this thesis will demonstrate, the grotesque's indeterminacy may provide a way to understand "reality" or the means to construct a better one.